FOUR NEW RECORDS OF PROSOBRANCH GASTROPODS FROM MANDAPAM - Unnithan, Asokakumaran (Indian Journal of Fisheries, 2011)
Four prosobranch gastropods Epitonium scalaris (Linnaeus), Capulus Sp.,Bursct crumena (Lamarck) and Turris indica Reding, recorded for the first time,from Mandapam area are described